KREATIVITAS DAN INOVASI PELAKU KUBE - Yuce Sariningsih (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This research concerning the program evaluation from Social Ministry of Republic of Indonesia which have conducted a productive economic activity in form of small business group, that is called Kelompok Usaha Bersama (KUBE) for the poor woman. It focused on reducing poverty in the context of building creativity and innovation as a main component of entrepreneurship. Another fact described that their welfare condition was in low level. The aim and purpose of this research was to analyze their creativity and innovation. The research has been conducted in West Java-Indonesia, and determined 111 (one hundred and eleven) respondents as sample. The research employed explanatory survey method and the data sources was primary and secondary data. A Questionnaire, observation and structured interview have been choosen for the data gathering techniques, and has been analyzed by path analysis. The research finding showed that respondent in condition lack of creativity and innovation and the recommendation has been formulated by improving the entrepreuneurial spirit of KUBE’s social advisor of KUBE.